2017
DOI: 10.1139/apnm-2016-0542
|View full text |Cite
|
Sign up to set email alerts
|

Excessive training is associated with endoplasmic reticulum stress but not apoptosis in the hypothalamus of mice

Abstract: Downhill running-based overtraining model increases the hypothalamic levels of IL-1β, TNF-α, SOCS3, and pSAPK-JNK. The aim of the present study was to verify the effects of 3 overtraining protocols on the levels of BiP, pIRE-1 (Ser724), pPERK (Thr981), pelF2α (Ser52), ATF-6, GRP-94, caspase 4, caspase 12, pAKT (Ser473), pmTOR (Ser2448), and pAMPK (Thr172) proteins in the mouse hypothalamus. The mice were randomized into the control, overtrained by downhill running (OTR/down), overtrained by uphill running (OTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
(61 reference statements)
1
9
0
2
Order By: Relevance
“…Regarding ATF6, mRNA levels were not changed in rat liver with the 6-week treadmill (Chapados & Lavoie, 2010). The same results were obtained in ATF6 levels in mice hypothalamus after 8-week voluntary running (Pinto et al, 2017). This could be explained by the fact that BiP levels depend on those of ATF6 (Borsa et al, 2015), which, in our case, was not increased by exercise.…”
Section: Discussionsupporting
confidence: 85%
“…Regarding ATF6, mRNA levels were not changed in rat liver with the 6-week treadmill (Chapados & Lavoie, 2010). The same results were obtained in ATF6 levels in mice hypothalamus after 8-week voluntary running (Pinto et al, 2017). This could be explained by the fact that BiP levels depend on those of ATF6 (Borsa et al, 2015), which, in our case, was not increased by exercise.…”
Section: Discussionsupporting
confidence: 85%
“…46,53 Thus, the increase in cardiac glycogen deposition after the 3 overtraining models may be considered a compensatory mechanism for the impairment of skeletal muscle signal transduction. 12,18 Because our overtraining models led to decreased performance and other negative responses in different tissues, 11,12,21,24,26,29,54,55 it is important to point out that upregulation of insulin signaling pathway components in mice hearts is also related to pathologic hypertrophy. [56][57][58] Therefore, further studies should evaluate whether these overtraining models lead to pathologic or physiologic cardiac hypertrophy.…”
Section: Resultsmentioning
confidence: 99%
“…In a study based in 3-weeks voluntary running with mice fed low-fat diet (LFD) or HFD, eIF2α mRNA expression was upregulated in brain and liver of high runners with both LFD and HFD, while peIF2α only increased in hippocampus of HFD-high runners (Kim et al, 2010). Similarly, 8-weeks running with different inclinations demonstrated that the downhill protocol increased peIF2α levels in mice EDL (Pereira et al, 2016) and hypothalamus (Pinto et al, 2017). By the contrary, 8-weeks swimming decreased peIF2α in HFD rat liver and AT, but not in control rats (da Luz et al, 2011).…”
Section: Exercise and Uprmentioning
confidence: 93%
“…Thus, 6-weeks endurance training increased PERK levels in mice soleus and liver (Deldicque et al, 2013) and 3-weeks running increased ATF6 mRNA expression in mice brain (Kim et al, 2010). Finally, 8-weeks running in downhill, uphill, or without inclination modified pPERK, pIRE1, and ATF6 levels in mice hypothalamus and muscles (Pereira et al, 2016; Pinto et al, 2017). However, contradictory results were also found in the two previous studies, depending on the tissue and the type of protocol employed.…”
Section: Exercise and Uprmentioning
confidence: 99%